Zonal Growth Pattern of the Prostate Is Affected by Age and Body Mass Index. Issue 4 (2nd April 2022) - Sharkey, Christina; Long, Xingbo; Wang, Zongwei; Al-Faouri, Ra'ad; Gershman, Boris; Tsai, Leo L.; Olumi, Aria F.
Abstract : Purpose: As men age, the prostate continues to grow on average 2.5% per year. While the variable growth rate of the total prostate gland is recognized, the growth rate of different prostate zones remains largely unclear. We evaluated the growth patterns of the prostate zones and identified clinical parameters contributing to the zonal growth rates. Materials and Methods: Prostate magnetic resonance imaging (MRI) data and clinical information were obtained retrospectively on 156 patients who had at least 3 prostate MRIs between 2003 and 2018. Different prostate zonal volumes were measured and analyzed. The outcome was analyzed using linear regression. Results: We observed that prostate growth rates vary depending on body mass index (BMI), transition zone index (TZI), the prostate zone and 5-alpha reductase inhibitor (5ARI) use. The peripheral zone volume growth rates increased with age and peaked at 60–70 years of age (p=0.047), while the transition zone volume demonstrates continuous growth without a peak through all ages. BMI and TZI are associated with the growth rate of the peripheral zone (p=0.026, p <0.001, respectively) but not the transition zone growth rate. 5ARI use is significantly associated with the reduction in the transition zone growth rate (p=0.033), not the peripheral zone. In addition, patients with TZI greater than 60% had the most significant reduction in the transition zone growth rate while taking 5ARI (p <0.001). Conclusions: Transition and peripheral zones of the prostate grow at variable rates. BMI and TZI affect peripheral zone growth rate, while 5ARI use reduces the transition zone growth rate.